Penguatan Ketahanan Pangan Lokal Melalui Budidaya Kailan Organik Di Desa Pasigaran Kecamatan Tanjungsari Kabupaten Sumedang - Intan Ratna Dewi Anjarsari; Uum Umiyati; Murgayanti Murgayanti (Journal of Empowerment Community, 2026)
Local food security is a key element in creating sustainable food self-sufficiency at the community level. Pasigaran Village, Tanjungsari District, Sumedang Regency has agricultural potential that can be optimized through organic cultivation of kailan (Brassica oleracea var. alboglabra). This Community Service activity aims to improve farmers' knowledge in implementing organic farming systems to support healthy food diversification and reduce dependence on synthetic chemical inputs. The methods used include socialization, organic cultivation training, technical assistance, and evaluation of program effectiveness. The results of the activities show that the implementation of organic cultivation techniques on kailan can improve soil fertility, reduce the negative impact of using chemical fertilizers and pesticides, and produce healthier products with high economic value. Pre-test and post-test evaluations showed significant improvements in farmers' understanding and skills regarding organic farming. Thus, the program contributes to strengthening local food security, improving farmers' welfare, and developing a more sustainable agricultural system in Pasigaran Village.